Low Compliance with Iron-Folate Supplementation Among Postpartum Mothers of Nepal: An Analysis of Nepal Demographic and Health Survey 2011 - Khanal, Vishnu; Adhikari, M.; Karkee, R. (Springer New York, 2014)
One in five maternal deaths are directly attributable to anaemia in the world. The World Health Organization recommends iron supplementation from the second trimester of pregnancy to 45 days after delivery. The aim of this study was to determine the compliance rate of iron-folate consumption and the factors associated with iron-folate consumption among post-natal mothers in Nepal. This study utilised the data of Nepal Demographic and Health Survey (NDHS) 2011. The NDHS 2011 is a cross sectional and nationally representative survey. Of the 4,148 respondents, only 20.7 % consumed iron throughout the post-natal period for 45 days. Mothers who had higher and secondary education [adjusted Odd ratio (aOR) 3.101; 95 % CI (2.268–4.240)]; had attended four or more antenatal care visits [aOR 9.406; 95 % CI (5.552–15.938)]; lived in Far-western development region [aOR 1.822; 95 % CI (1.387–2.395)]; delivered in health facility [aOR 1.335; 95 % CI (1.057–1.687)]; and attended postnatal care [aOR 2.348; 95 % CI (1.859–2.965)] were more likely to take iron for 45 days of postpartum. Intervention to increase the compliance with the postpartum iron-folate supplementation are required to avoid adverse pregnancy outcomes associated with poor iron status with especial focus on the mothers who delivered at homes and did not attend postnatal check up.